Evaluation of volleyball statistics with multidimensional scaling analysis - Zirhlioglu, G. (International Journal of Sports Science and Engineering, 2013)
The purpose of this study was to investigate the playing characteristics of team performance in Turkey Women`s Voleyball. So, it was used some statistical values of team performance. These statistical values are break point, serve error, ace, reception error, reception excellent, attack error, attack block, attack points and block points. 149 female matches of the Turkish AROMA Voleyball League were analyzed. The data was obtained from web site of the Turkish Voleyball Federation. Ace, reception excellent and attack points are variables which are positive in the first dimension and negative in the second dimension play role in determining the performance of teams.